Genetic Interactions between the Coagulation and Fibrinolytic Systems - Degen, Jay L. (Thrombosis and Haemostasis, 2001)
Nearly all of the genes encoding the established coagulation and fibrinolytic factors have been successfully altered or disrupted in transgenic mice. Although comprehensive studies of each of these genetargeted mouse lines are still ongoing, the initial findings have significantly refined our understanding of the roles of selected hemostatic factors in vivo, and occasionally altered long-standing concepts. This review summarizes some of the progress that has been made in the generation and phenotypic characterization of mice lacking key hemostatic factors, including coagulation, fibrinolytic, platelet and endothelial cell-associated factors. New insights regarding the role(s) and interplay of hemostatic factors that have emerged from detailed studies of mice carrying multiple deficits in coagulation and fibrinolytic system components are highlighted.
Keywords: Coagulation; fibrinolysis; platelets; gene-targeting